TI_GERICHTE 15.2019.21 vom 30. Juli 2019 , Pignoramento successivo di beni nuovamente scoperti. Termine di perenzione - TI Tribunale d'appello (2019)
Pignoramento successivo di beni nuovamente scoperti. Termine di perenzione